GEDUNG PERTUNJUKAN SENI DI BANJARBARU - Mustika, Wulan; Aufa, Naimatul (UNIVERSITAS LAMBUNG MANGKURAT, 2025)
In South Kalimantan, especially in Banjarbaru City, art has developed rapidly. This can be seen from the existence of the Campus Art Workers Communication Forum (FKPSK), as well as many art studios, communities, and associations that are active in preserving regional cultural arts. In addition, Banjarbaru also regularly hosts various art activities that are recorded in the Banjarbaru Calendar of Events, making it a dynamic city in promoting arts and culture. In an effort to support these developments, the design of the Banjarbaru Performing Arts Center will apply the Banjar Locality Architecture concept as the main approach. This concept is chosen to reflect the local cultural identity, particularly the traditional character typical of South Kalimantan. To create a building that functions as an art center and a visual representation of Banjar culture, traditional architectural elements, such as the shape of the Gajah Manyusu House and the manyusu elephant roof, will be used. The application of locality architecture in this building aims to support the preservation of local culture. With a design that integrates traditional elements, this building is expected to be able to introduce and instill pride in ancestral heritage, especially to the younger generation as well as meet the needs of the building users.